(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The geographical factors played an important role in the evolution and growth of the military system of the Delhi Sultanate. These factors include the plains, mountains, hills, forests, deserts, rivers, climate, sea and routes.